Sentidos da vulnerabilidade no contexto da deficiência a partir da análise de decisões judiciais - Sílvia Pires Volpini (2023)
This study aims to investigate whether there is a normative meaning in the idea of vulnerability used in judicial decisions that deal with the rights of people with disabilities. To understand the issue, the decision analysis methodology is adopted with a specific focus limited to judgments on civil matters by the STJ and TJMG. It starts from the hypothesis that vulnerability is a fluid and dynamic concept, whose manifestation varies according to the circumstances of the concrete situation, thus allowing for many possible responses to its mitigation. Despite this, in cases involving people with disabilities, judicial courts assumes the presence of vulnerability, adopting it as a generic or vague basis for adjusting normative provisions to the need for protection. Through the jurisprudential survey, the thematic contexts in which vulnerability is presented were identified, the different aspects through which the notion is assimilated, the tendency of the judgment results and the effects of the use of the word in the argumentative line adopted by the judge. The decision-making foundations, in general, intuitively link the condition of vulnerability to the person with a disability, without any interpretation or complementation in this regard. Thus, the risk of rhetorical manipulation of vulnerability imposes on interpreters the urgent task of re-discussing and refining the concept, in order to prevent its emptying. It appears that vulnerability has a promising operative character in the legal sphere to identify situations in which the rights of people with disabilities are violated and which is the most appropriate instrument to promote protection and safeguard autonomy.